2016
DOI: 10.1093/ckj/sfw013
|View full text |Cite
|
Sign up to set email alerts
|

Dialyzing women and men: does it matter? An observational study

Abstract: BackgroundApplication and consequences of hemodialysis treatment may differ between genders; focusing on these differences may be useful to optimize outcomes.MethodsData from 1 999 648 hemodialysis sessions performed in 10 984 (3316 incident and 7668 prevalent) patients, treated in 55 centers of the European Clinical Database (EuCliD)–Turkey, were analyzed, and various demographic, clinical, biochemical, therapeutic and prognostic parameters were compared.ResultsThere were 1905 male and 1411 female incident an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
2
8
4
1
Order By: Relevance
“…Similar findings were seen in a study in which females are found to have a greater risk of death [ 17 ] with an adjusted risk odds ratio of 3.9, and this difference remained significant in a multivariate analysis [ 18 ]. This is in contrast with findings that demonstrated no significant difference for survival between dialyzing women and men [ 19 , 20 ]. The results of our observational study revealed discrimination in the dialysis of men and women.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were seen in a study in which females are found to have a greater risk of death [ 17 ] with an adjusted risk odds ratio of 3.9, and this difference remained significant in a multivariate analysis [ 18 ]. This is in contrast with findings that demonstrated no significant difference for survival between dialyzing women and men [ 19 , 20 ]. The results of our observational study revealed discrimination in the dialysis of men and women.…”
Section: Discussioncontrasting
confidence: 99%
“…There is controversy over the association of gender with the mineral parameters in patients with chronic kidney disease. In contrast to our study, Artan et al (2016) reported that control of serum phosphorus was better in women compared to men [4]. The main reasons are probably the efficiency of dialysis, which results in greater phosphorus clearance, compliance with a strict diet and/or better adhesion to phosphate binders [4].…”
Section: Resultscontrasting
confidence: 84%
“…However, when kidney failure becomes chronic, through gradual progression -over a period of weeks, months or years -the kidneys slowly stop functioning, there is a terminal kidney disease [3]. An adequate treatment protocol must take into account gender differences, since not only demographic characteristics, but also many clinical, laboratory and therapeutic parameters can affect morbidity and mortality and differ considerably between the two genders [4].…”
Section: Introductionmentioning
confidence: 99%
“…In our study non-ESA patients presented with higher IBWG values. IBWG was increased in men more than it was in women (22), and since our non-ESA group had a higher ratio of men it might explain the difference.…”
Section: Discussionmentioning
confidence: 61%